The Paradigm of Termination of Employment Relationship Againts Worker/Labor Suspected in Criminal Action - Peter Jeremiah Setiawan; Xavier Nugraha; Elma Putri Tanbun (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
After the issuance of Law Number 11 of 2020 on Job Creation, several policies in Indonesia are amended, including the Manpower Law, especially regarding the termination of employment relationship on worker/labor suspected of committing a criminal action. This research is a normative legal research that uses a statutory approach and a conceptual approach. The result of this research shows that there has been a change of paradigm on the policy of termination of employment relationship against worker/labor suspected of committing a criminal action, which previously was based on the principle of presumption of guilt and became the principle of efficiency of justice. This happened since the policy on the termination of employment relationship based on the principle of presumption of guilt creates several issues, such as the lengthy period to wait for a legally binding decision, employers are unable to get a substitute worker/labor, worker/labor who has not been working in a long period will find difficulties when he returns to work.